2009
DOI: 10.1111/j.1438-8677.2008.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Ice encapsulation protects rather than disturbs the freezing lichen

Abstract: Arctic and alpine terricolous lichens are adapted to harsh environments and are tolerant to extremely low temperatures when metabolically inactive. However, there are reports indicating that freezing can be lethal to metabolically active lichens. With a projected warmer and more unstable climate, winter precipitation at high latitudes will fall more frequently as rain, causing snowmelt and encapsulating terricolous lichens in ice or exposing them to large temperature fluctuations. Lichens are a major winter fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The majority of studies investigating the impacts of icing events have focussed on agriculturally significant plant species [e.g. wheat, cranberry; Andrews and Pomeroy (1975), Schluter and Crawford (2003)], and of the few studies on arctic and Antarctic plants, all have been conducted as laboratory studies or using pot‐grown plants (Bjerke 2009, Zuniga‐Feest et al 2009) and anoxia (Crawford et al 1994). One of these studies demonstrated the benefits of ice encapsulation on arctic lichens, with ice‐encased lichens showing improved photosynthetic performance compared to lichens left uncovered (Bjerke 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating the impacts of icing events have focussed on agriculturally significant plant species [e.g. wheat, cranberry; Andrews and Pomeroy (1975), Schluter and Crawford (2003)], and of the few studies on arctic and Antarctic plants, all have been conducted as laboratory studies or using pot‐grown plants (Bjerke 2009, Zuniga‐Feest et al 2009) and anoxia (Crawford et al 1994). One of these studies demonstrated the benefits of ice encapsulation on arctic lichens, with ice‐encased lichens showing improved photosynthetic performance compared to lichens left uncovered (Bjerke 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2). To our knowledge very few research have been carried out on the effects of snow and ice metamorphism on dwarf shrubs and ground lichen and vice et versa (Bjerke, 2009;Tømmervik et al, 2009). It could be important for both reindeer husbandry and forestry if research was developed on this topic.…”
Section: Resultsmentioning
confidence: 99%
“…The main food source of these reindeer, lichens, may also be affected by the formation of ice especially if they become encased in ice. Bjerke (2009) performed an icing experiment on three lichens species of importance for reindeer feeding: Cladonia rangiferina, C. stellaris and Flavocetraria nivalis and found that ice encapsulation did not affect these lichens. However, at mild subfreezing (-1.5°C) temperatures, the ice-encased lichens had reduced photosynthetic and chlorophyll fluorescence rates (70 %) suggesting a deterioration of the algal partner.…”
Section: Changes In the Snow Profilementioning
confidence: 99%